Teaching English Writing for Primary Students: Constructivism Views - Aprilianti, Berliana Dyah Ayu (JET (Journal of English Teaching), 2024)
As one of the productive skills, writing is highly required to be mastered by English as foreign language. Moreover, communication can be occurred not only in spoken form but also in written form. In creating good learning atmosphere for the students, teachers try to use the most appropriate approach to aim the learning goals, especially in mastering the writing skill. Constructivism approach is commonly used by teachers to enhance it. The implement of constructivism in teaching writing emphasize on students’ activity in building knowledge, interacting with others, constructing ideas, presenting critical thinking and collaboration. Those elements from constructivism are also integrated use teaching method that has been implemented by the teachers. However, teaching writing for primary students level is challenging in many context. Therefore, this article presents a closer look of the constructivism views for teaching primary students’ English writing. The implication from this article is hoped to be used as the supplementary information for primary teachers and other researchers on similar topic in teaching writing using constructivism approach.